Relationships between proactive personality and creativity: Mindsets and golden mean thinking as parallel mediators among Chinese third language students - Deng, Weipeng; Dai, Yanjing; Gao, Yuhong; Lin, Rongxin; Lei, Fei; Lei, Lin (Frontiers in Psychology, 2022)
Third language (L3) learners have great potential in developing creativity; however, the factors affecting L3 learners’ creativity have received little attention. This study investigated the relationships between proactive personality, three different thinking patterns (i.e., growth mindset, fixed mindset, and golden mean thinking), and creativity among L3 learners. The participants were 220 Chinese students who attended an obligatory L3 course in college. The results showed that proactive personality, growth mindset, golden mean thinking, and creativity had significant intercorrelations. Moreover, the role of growth mindset and golden mean thinking as mediators of the proactive personality and creativity relation was supported, and the mediating effect of growth mindset was larger than that of golden mean thinking. However, the fixed mindset did not show a significant indirect effect on the path from proactive personality to creativity. This is the first research to treat growth mindset, fixed mindset, and golden mean thinking as mediating variables on the path from proactive personality to creativity, particularly demonstrating that golden mean thinking, which is specific to Asian students and located midway between a growth mindset and a fixed mindset, can cultivate creativity. Some suggestions for fostering creativity in L3 students were also included in this study.